Effect of Allopurinol and Inosine Administration on Xanthine Oxidoreductase Gene Expression in Selected Tissues of Broiler Chickens - Settle, T.; Falkenstein, E.; Klandorf , H. (International Journal of Poultry Science, 2014)
Uric acid is considered the most significant factor in amelioration of oxidative burden in birds. Uric acid is formed in the terminal reactions of purine degradation by the enzyme xanthine oxidoreductase (XOR). In this study, inosine, a purine precursor, was fed to 3 groups of 5 birds: Group 1 was fed 0 (control), Group 2, 0.6 mols inosine/kg feed (INO) and Group 3, INO treatment plus 50 mg allopurinol/kg BM (INOAL). Allopurinol is a known inhibitor of XOR and thereby reduces uric acid (UA). INOAL birds showed lower total liver XOR activity (p = 0.005) but kidney XOR activity was not affected. Both INO and INOAL treated birds had higher plasma and kidney UA concentrations than controls. Liver uric acid (LUA) was significantly reduced in INOAL birds when compared to other treatments. XOR gene expression was increased (p = 0.007) in the liver tissue of INOAL birds when compared to CON and INO birds. However, there were no significant changes in XOR gene expression in the kidney tissue. To our knowledge, this is the first report of XOR gene expression measured under these conditions. These results suggest that regulation of UA production is tissue dependent. The results also indicate a compensatory effect of allopurinol on XOR gene expression which can be linked to a decrease in antioxidant protection from UA.